Pemanfaatan limbah kopolimer ethyene vinyl acetateuntuk komposit karet - Nurhajati, Dwi Wahini (Majalah Kulit, Karet, dan Plastik, 2008)
A new composite of natural rubber blend with ethylene vinyl acetate (EVA) waste obtained from footwear industry hase been made. EVA waste from footwear industry is crosslinked materials which is able to be used as a filler in composite rubber. Potency of EVA waste in the form of powder from the footwear industry in Indonesia is more than 50kg/day, while in the form of solid is about 75,000 ton/ year and is hasnât yet utilized. The aim of this research is to study influence of EVA waste on the physical properties of natural rubber composite filled with EVA waste. Natural rubber, EVA waste, and addives were mixed by a two-roll mills machine. TheÂ  amounts of EVA waste were varied from 0 to 100 phr with range of 20 phr. The results of physical properties test showed that the maximum addition of EVA waste, which performed highest tensile strength, and tear resistance was found for 60 phr, and which contributed to an increase in higher elongation at break, hardness, 50% permanent set, and density was found for 100 phr. The addition of EVA waste resulted in a reduction of the abrasion resistance. All of the resulted composites there were no crack detected on the flex cracking test at 150 kcs. Â Â Key words: Composites, natural rubber, EVA waste, physical properties. Â  Â ABSTRAKÂ Telah dibuat komposit baru dari campuran karet alam dengan limbah kopolimer ethylene vinyl acetate (EVA) yang berasal dari industri alas kaki. Limbah EVA dari industry alas kaki merupakan bahan yang telah terikat silang yang dapat digunakan sebagai bahan pengisi (filler) untuk komposit karet. Di Indonesia limbah EVA yang dihasilkan dalam bentuk serbuk lebih dari 50 kg/hari, sedangkan yang berbentuk padat sekitar 75.000 ton/tahun dan belum dimanfaatkan secara optimal padahal limbah EVA dapat digunakan sebagai bahan pengisi untuk komposit karet. Tujuan penelitian adalah mempelajari pengaruh jumlah limbah EVA terhadap sifat fisis komposit karet alam-limbah EVA. Karet alam limbah EVA dan bahan aditif dicampur dalam mesin two-roll mills. Jumlah limbah EVA, divariasi dari 0 sampai 100 phr dengan kisaran kenaikan 20 phr. Hasil uji sifat fisis komposit menunjukkan bahwa penambahan sampai dengan 100 phr menaikkan perpanjangan putus, kekerasan perpanjangan tetap 50%, dan bobot jenis. Penambahan limbah EVA pada pembuatan komposit karet alam ini menyebabkan ketahanan kikis komposit turun. Semua komposit campuran karet alam dan limbah EVA hasil percobaan tidak retak ketika dibengkuk sampai 150 kcs.Â Kata kunci: komposit, karet alam, limbah EVA, sifat fisis.Â